PENGARUH BIMBINGAN BELAJAR ORANGTUA TERHADAP DISIPLIN BELAJAR SISWA SEKOLAH DASAR - Maria Finsensia Ansel; Natalia Pawe (Program Studi PGSD Universitas Flores, 2021)
The purpose of this study was to determine the effect of parental tutoring on the learning discipline of elementary school students in group, Kelimutu sub-district. The approach in this research is done quantitatively with the research method is correlational research. The research population was all elementary school students in group 1, Kelimutu sub-district, Ende district, as many as 432 students with a purposive sampling technique, so that the sample in this study were students in grades IV-VI of elementary school group 1, Kelimutu district, totaling 80 people. The data collection method used a questionnaire, namely a parent learning guidance questionnaire and a student learning discipline questionnaire. Analysis of research data was carried out to test descriptive statistics, test data normality and test data linearity, as well as test hypotheses. The results showed that the value of the regression equation Y=4.677+0.931 indicates the direction of the regression equation is positive. The value of F count = 325.726 > F table = 3.96 with a significance value of 0.000 <0.05, meaning that there is a significant effect of the parental tutoring variable on the student learning discipline variable. The coefficient of determination test obtained an Rsquare value of 0.807 or 80.7%, meaning that student learning discipline is influenced by parental tutoring with a magnitude of influence of about 80.7% showing a very strong influence while the rest is influenced by other factors. In conclusion, the higher the parental guidance, the higher the student's learning discipline, on the contrary, the lower the parental guidance, the lower the student's learning discipline.